Students' Abilities in Analyzing Deixis in Coldplay Song "Viva la Vida" - Taolin, Luciana Ludowika Ignanita; Misa, Mikhael; Yulita, Delti (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
This study aims to explore the ability of second-grade students at SMAN 1 Kefamenanu to identify and analyze deixis in the lyrics of the popular song "Viva la Vida" by Coldplay. Deixis refers to words whose meanings depend on the context of the speaker, listener, or situation, and in this study, three types of deixis were examined: personal, spatial, and temporal. A quantitative descriptive design with a case study approach was used, focusing on 14 students from grade XI. Data collection methods included written tests, observations, interviews, and documentation of students' work. Students were tasked with identifying examples of personal, spatial, and temporal deixis in song lyrics. The results revealed that personal deixis was the most dominant, with an average score of 72.71%, indicating a strong understanding among students in this category. Temporal deixis followed with an average score of 55.71%, indicating that students were generally able to identify time-related references in the song. In contrast, spatial deixis received the lowest mean score of 41.71%, indicating that students faced difficulties in understanding or identifying spatial references, which may require higher contextual awareness. The findings suggest that although students are proficient in recognizing personal and temporal deixis, more emphasis should be placed on teaching spatial deixis. This study highlights the effectiveness of using popular music, such as “Viva la Vida,” in improving students’ understanding of the use of deixis and offers insights into how song lyrics and deixis can be integrated into language learning.